Setting Up Workflow of an Intraoperative MRI Unit: A Single-Centre Experience of First 53 Cases - Manohar, Nitin; Mohapatra, Deviprasad; Balasubramaniam, Anandh; Rao, Keerthi; Srinivas, Deepti; Chakrabarti, Dhritiman (Journal of Neuroanaesthesiology and Critical Care, 2018)
Background Setting up of a new “nearby” operation room type intraoperative magnetic resonance imaging (iMRI) unit poses a unique set of challenges to the operating team. We describe here an account of our experiences and a step by step protocol designed by us and followed to troubleshoot the issues encountered. The primary objective of the study was to observe our learning curve in the process of setting up of a new iMRI unit. The secondary objectives were to look at the number of residues detected, quality of imaging, and complications during iMRI.Materials and Methods An observational study was conducted over a 3-month period involving cases requiring iMRI. Initially, a simulation was performed using healthy volunteers, which helped in developing a systematic protocol and drafting checklists to ensure a smooth workflow pattern. Data collection included details regarding hindrances encountered, how these were tackled, iMRI details (residual tumor, re-surgery), and complications, if any.Results A total of 53 cases underwent iMRI in the study period. Among these, 51 were tumor cases that revealed residue (detected in 28 [54.9%] cases), and re-surgery for further resection was performed in 21/28 (75%) cases. A very high level of surgeons’ satisfaction regarding image quality of intraoperative scan was recorded (45/53 [84%]). The number of personnel required for shifting and shifting times could be reduced with efficient utilization of the checklist.Conclusion A methodical approach to tackle impediments while setting up a new unit such as iMRI facilitates its smooth functioning and ensures minimal interruptions and evades undue complications.
Keywords: intraoperative magnetic resonance imaging; operating room magnetic resonance imaging; image-guided neurosurgery